Oral Ivermectin versus Single Topical Permethrin in the Treatment of Scabies - Kamruzzaman; Rahman, Morshedur; Baidya, Manashi; Faisal, HW; Rahman, Mahmudur; Kadir, Abdul (The Planet, 2023)
Background: Scabies is a highly contagious and intenselypruritic parasitic infestation. It is a re-emerging infectionin the new millennium especially in developing countries.Various treatment modalities have been used and topicaltreatment i.e. 5% permethrin is the most effective scabicidewith few side effects. Ivermectin is the only oral scabicideavailable. Objectives: This study compares the efficacy oforal ivermectin with topical permethrin cream in thetreatment of scabies. Methods and materials: Thisobservational study was conducted at the out-patientdepartment of Dermatology and Venereology at Sher-EBangla Medical College Hospital, Barishal over a periodof 8 months. A total of 130, otherwise healthy, patientswith scabies, aged 18-65 were Institutions such as nursinghomes, extended-care facilities, and prisons are often sites ofscabies outbreaks. Child care facilities also are a common site of scabies infestations[2,3]enrolled studyand randomly divided in 2 groups of 65 each receiving either topical 5% permethrin (groupA) or oral ivermectin (200 μg/kg/dose) in a single dose (group B). All the patients werefollowed up at day 7 and 14. Assistant Professor, Department of Paediatrics, Sher-E-Bangla MedicalCollege, Barishal, Bangladesh. Results: At day 7, cure rate was similar in two groups (p=0.49) [Table 2]. Marginally, more patients in group A had very good response as compared togroup B. Final assessment was made at day 14. Results revealed 67.9% patients in group Aand 65.3% patients B had cure (p=0.87). Treatment failure was also similar in both groups(p=0.9) Conclusion: Both permethrin and ivermectin in both single and single dose regimenare equally efficacious and well tolerated in scabies. However, permethrin has a rapid onsetof action.